Pengembangan SDM Humas untuk Meningkatkan Keterampilan Komunikasi dan Networking di Desa Sukaragam - Fifi Hanafia; Catur Sasi Kirono; Supartono . (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Youth empowerment through strengthening leadership capacity is a strategic issue in supporting sustainable rural development, particularly in the context of Generation Z, which is highly adaptive to digital technological advancements. This community service activity aims to examine the implementation of a human resource development seminar in enhancing leadership competencies and organizational management skills among members of the Karang Taruna of Sukaragam Village. The study employs a descriptive qualitative approach using participatory observation, in-depth interviews, and documentation. The stages of the program include needs analysis, seminar design and implementation, activity evaluation, and report and documentation preparation. The results indicate an improvement in participants’ understanding of adaptive leadership, increased organizational motivation, and the strengthened role of public relations in building communication and collaborative networks with various stakeholders. Furthermore, the seminar received positive support from local government and the community. This community service contributes meaningfully to youth empowerment and the strengthening of social organizations at the village level, and serves as a foundation for recommendations for sustainable and replicable leadership training programs in other rural areas.